HUBUNGAN ANTARA KEBIASAAN MEMBACA DENGAN KEMAMPUAN MENULIS KARANGAN SISWA KELAS 4 SEKOLAH DASAR: HUBUNGAN ANTARA KEBIASAAN MEMBACA DENGAN KEMAMPUAN MENULIS KARANGAN SISWA KELAS 4 SEKOLAH DASAR - Niky Herlina; Hafiaturrahmah; Nursina sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between reading habits and essay writing skills of grade IV elementary school students. The method used was descriptive qualitative research with data collection techniques through observation, interviews, and documentation which were then analyzed using the Miles and Huberman interactive model. The results of the study show that students with good reading habits have more structured, coherent, and vocabulary-rich essay writing skills than students who rarely read. This finding confirms that reading habits play an important role in improving writing skills. For future research, it is suggested that further studies be conducted by involving a wider number of subjects and combining quantitative approaches, so as to provide more comprehensive results regarding the contribution of reading habits to the writing skills of elementary school students